Energy and nutrient issues in athletes with spinal cord injury: Are they at risk for low energy availability? - Figel, K.; Pritchett, K.; Pritchett, R.; Broad, E. (Nutrients, 2018)
Low energy availability (LEA) and nutrient intake have been well studied in able-bodied athletes, but there is a lack of research examining these issues amongst athletes with spinal cord injury (SCI). To date, there have been no studies that have examined energy availability (EA) amongst this population. Furthermore, athletes with SCI may experience unique challenges around nutrition that may increase their risk of LEA. This review will evaluate the literature and assess whether this population is at risk for LEA. Due to the limited research on this topic, sedentary individuals with SCI and para athletes were also included in this review. Review of the current literature suggests that athletes with SCI may be at an increased risk for LEA. While research examining EA and risk of LEA in athletes with SCI is lacking, the number of athletes with SCI continues to increase; therefore, further research is warranted to assess nutrient and energy needs and their risk to this population